Integrating nutrition into the education sector in low‐ and middle‐income countries: A framework for a win–win collaboration. Issue 3 (16th February 2021) - Xu, Yvonne Yiru; Sawadogo‐Lewis, Talata; King, Shannon E.; Mitchell, Arlene; Roberton, Timothy
Abstract: Malnutrition—both undernutrition and overnutrition—is a public health concern worldwide and particularly in low‐ and middle‐income countries (LMICs). The education sector has high potential to improve immediate nutrition outcomes by providing food in schools and to have more long‐term impact through education. We developed a conceptual framework to show how the education sector can be leveraged for nutrition. We reviewed the literature to identify existing frameworks outlining how nutrition programs can be delivered by and through the education sector and used these to build a comprehensive framework. We first organized nutrition programs in the education sector into (1) school food, meals, and food environment; (2) nutrition and health education; (3) physical activity and education; (4) school health services; and (5) water, sanitation, and hygiene (WASH) sector. We then discuss how each one can be successfully implemented. We found high potential in improving nutrition standards and quality of school foods, meals and food environment, especially through collaboration with the agriculture sector. There is a need for well‐integrated, culturally appropriate nutrition and health education into the existing school curriculum. This must be supported by a skilled workforce—including nutrition and public health professionals and school staff. Parental and community engagement is cornerstone for program sustainability and success. Current monitoring and evaluation of nutrition programming in schools is weak, and effectiveness, including cost‐effectiveness, of interventions is not yet adequately quantified. Finally, we note that opportunities for leveraging the education sector in the fight against rising overweight and obesity rates are under‐researched and likely underutilized in LMICs.